1994
DOI: 10.1136/jnnp.57.3.320
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of epilepsy in a largely untreated population in rural Ecuador.

Abstract: A house-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(52 citation statements)
references
References 27 publications
6
44
0
1
Order By: Relevance
“…Previous papers ad dressing the problem of the EEG findings and the risk of chronic epilepsy did not yield sig nificant results [4,15,17], While a negative association between the prospect for seizure control and the number, frequency or duration of the seizures before therapy has been consistently reported [4,6,17,21], the present study showed a lack of any such association between seizure outcome and the number of seizures before the begin ning of treatment, in agreement with Sillanpaa [6], Therefore, while there is no doubt that the prognosis for seizure control is inversely pro portional to the disease duration, the role of early treatment has not been yet resolved [10]. On the other hand, the outcome of epilepsy might simply mirror the natural history of the disease which may be inherently more or less severe: the high rate of spontaneous inactivity seen in patients never treated [22] would offer circumstantial evidence in favour of this statement. The conflicting results, however, could be related to a lack of uniformity in methodology, case selection and inclusion (type of epilepsy, age groups considered, etc.)…”
Section: Prognosis Of Childhood Epilepsymentioning
confidence: 70%
“…Previous papers ad dressing the problem of the EEG findings and the risk of chronic epilepsy did not yield sig nificant results [4,15,17], While a negative association between the prospect for seizure control and the number, frequency or duration of the seizures before therapy has been consistently reported [4,6,17,21], the present study showed a lack of any such association between seizure outcome and the number of seizures before the begin ning of treatment, in agreement with Sillanpaa [6], Therefore, while there is no doubt that the prognosis for seizure control is inversely pro portional to the disease duration, the role of early treatment has not been yet resolved [10]. On the other hand, the outcome of epilepsy might simply mirror the natural history of the disease which may be inherently more or less severe: the high rate of spontaneous inactivity seen in patients never treated [22] would offer circumstantial evidence in favour of this statement. The conflicting results, however, could be related to a lack of uniformity in methodology, case selection and inclusion (type of epilepsy, age groups considered, etc.)…”
Section: Prognosis Of Childhood Epilepsymentioning
confidence: 70%
“…In practice, there has been no agreement on an absolute number of seizures required for them to be considered recurrent. A few researchers have defined the term "epilepsy" to include patients with a single seizure, [27][28][29] and a few have required three unprovoked seizures. 30,31 Most recent clinical and epidemiologic studies have required two unprovoked seizures as a minimal criterion for the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…solium , and to answer a 14-question neurologic survey to screen for a history of seizures and headaches (appendix); the survey was completed by a parent or legal guardian if the participant was less than 12 years old. This survey was developed in Ecuador and later validated in Peru [11, 1315]. We offered in-home clinical evaluation by a neurologist to all participants who screened positive for a history of seizures or severe headaches.…”
Section: Methodsmentioning
confidence: 99%